RELAKSASI PAJAK : DAMPAK NEGATIF VIRUS CORONA PADA SEKTOR EKONOMI - Andini, Isnani Yuli; Arfiyanto, Dedy (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2022)
Covid-19 or what we are more familiar with as the corona virus whose spread is increasingly global has an impact on the economic sector. World economic growth is projected to contract further. For this reason, the government pays attention to issues that require special policies. These issues are, among others, related to the availability of food stocks and supplies that will affect food price stability; restrictions on travel and worker mobility affecting the tourism and transport sectors; production, distribution, and supply chain disruptions that affect the performance of the manufacturing sector and its derivatives. In Sumenep Regency, which is a Regency in the East End of the island of Madura, which is also affected by the Covid-19 Virus